Computer use of an assist , to learn the skill of rolling , in football - Mohammed, Saher (Journal of Physical Education, 2015)
The study aimed to: identify the impact of a computer to learn the skill of rolling football. The researcher used the experimental method on the research sample of elected breeding Anbar football average composed of 16 players divided into two groups, a control group and the experimental group used the experimental group computer as an aid to learning the skill of rolling football, while the control group used the approach to learning and achieve Researcher to outweigh the experimental group on the control group in learning the skill of rolling football as the use of computers has increased the desire of students and enforced toward learning